2012
DOI: 10.1177/0001699311431595
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem of academic and vocational students: Does within-school tracking sharpen the difference?

Abstract: Research into the effects of ability grouping has usually been conducted within schools. In the British and North American context, where the bulk of this kind of research has been carried out, ability grouping commonly occurs within schools. In Flanders – the Dutch-speaking, northern part of Belgium – as in other European countries, there are not only tracks within schools, but schools themselves can be distinguished by the curriculum they offer. This study questions whether students’ global self-esteem is af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 50 publications
3
84
0
3
Order By: Relevance
“…Second, especially in the case of retention's effects on adolescent deviancy, the stable unit treatment value assumption (Rubin, 1986) cannot be maintained. Previous research has hinted that structural school characteristics, such as the tracking system (Van Houtte, Demanet, & Stevens, 2012), and compositional characteristics, such as socioeconomic status (SES) and ethnic composition (Demanet & Van Houtte, 2011), may shape students' frame of reference for making social comparisons. Similarly, we may expect the percentage of retained students at a school to shape the nature of the social comparison process, which may affect the relation between grade retention and school misconduct.…”
Section: Grade Retention and School Misconductmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, especially in the case of retention's effects on adolescent deviancy, the stable unit treatment value assumption (Rubin, 1986) cannot be maintained. Previous research has hinted that structural school characteristics, such as the tracking system (Van Houtte, Demanet, & Stevens, 2012), and compositional characteristics, such as socioeconomic status (SES) and ethnic composition (Demanet & Van Houtte, 2011), may shape students' frame of reference for making social comparisons. Similarly, we may expect the percentage of retained students at a school to shape the nature of the social comparison process, which may affect the relation between grade retention and school misconduct.…”
Section: Grade Retention and School Misconductmentioning
confidence: 99%
“…Students in vocational tracks are more likely to have been retained in the past (Juchtmans et al, 2011). Hence, attending a vocational track in Flanders is rarely a positive choice, and vocational students are all too aware of their low status in society, leading to more anti-school attitudes and misconduct (for an extended discussion of the Flemish tracking system, see Van Houtte et al, 2012;Van Houtte & Stevens, 2008).…”
Section: Grade Retention and School Misconductmentioning
confidence: 99%
“…The global self-esteem scale is the most widely used definition and measurement of self-esteem. This holds also true for studies in Belgium (see for instance Van Houtte et al, 2012). The scale consists of 12 items with 5 possible answers ranging between 1 = absolutely disagree and 5 = totally agree.…”
Section: Variablesmentioning
confidence: 80%
“…That is, Verkuyten and Thijs also found that the share of ethnic minority pupils at school was positively related to the selfesteem of ethnic majority (native Dutch) pupils, although it did not have an effect on the self-esteem of ethnic minority pupils. The positive effect of ethnic minority concentration on native Belgian pupils' self-esteem can be framed by the reference group theory and be explained by the social comparison processes (see Van Houtte et al, 2012). That is, in schools with a larger ethnic minority concentration, native pupils are likely to experience relative gratification as they compare themselves with their less esteemed ethnic minority peers.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Slow-tracked students have also been shown to have elevated levels of psychological stress, such as anxiety and depression (Kokko et al, 2006;Wang et al, 2015). Other work documents that student self-esteem and confidence are significantly correlated with their position in the tracking system (Oakes, 1985;Van Houtte et al, 2012). In response to some of these negative proximate outcomes, it has been shown that slow-tracked students in tracked systems often become more aggressive, more impulsive, and exhibit more antisocial behavior (Kokko and Pulkkinen, 2000;Kokko et al, 2006).…”
Section: Hanushek 2006)mentioning
confidence: 99%